Girls play basketball too? A study of the mechanisms of traditional social gender consciousness on female participation in contact leisure sports - He, Yushan; Su, Guibin; Wang, Lujuan; Qian, Haonan (Frontiers in Psychology, 2024)
Background With the development of women’s sports, the mechanism of barriers to women’s leisure sports participation has attracted extensive attention from the academic community. Despite its significant impact, there are few empirical studies on intra-personal barriers. Consequently, a structural equation model was established to examine the relationships between traditional social gender awareness, gender bias, gender stereotypes, and barriers to participation in leisure sports. Methods In this study, a total of 508 questionnaires were collected and analyzed using AMOS 24.0 software for structural equation modeling. After model testing, the relationships between the variables were examined. Results The results of the statistical analyses indicated that traditional gender awareness could serve as an antecedent variable for barriers to participation in leisure sports, and that gender stereotypes mediated the relationship between traditional gender awareness and barriers to participation in leisure sports. The study also concluded that gender bias could not mediate the relationship between traditional gender awareness and participation barriers in leisure sports, but gender bias and gender stereotypes could act as chain mediators in the process of the influence of traditional gender awareness on barriers to contact leisure sports. Discussion This study emphasizes the need for women to break down the traditional social gender awareness, gender bias, gender stereotypes, and other intra-personal barriers when engaging in leisure sport participation. According to this study, the promotion of sustained and healthy development of women’s sport requires the breaking down of traditional social gender awareness education and the creation of more gender-inclusive sports policies and environments. The significance of the study is that by proposing and confirming the internal participation barriers to women’s participation in contact leisure sports, it will lead to the ideological liberation of women’s gender perspectives, so that they can break down the participation barriers to contact leisure sports, participate in sports activities, and enjoy the right to play sports on an equal footing.